2012
DOI: 10.1002/anie.201108690
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assemblies of Perylene Bisimide Dyes in Water

Abstract: Perylene bisimides are among the most valuable functional dyes and have numerous potential applications. As a result of their chemical robustness, photostability, and outstanding optical and electronic properties, these dyes have been applied as pigments, fluorescence sensors, and n-semiconductors in organic electronics and photovoltaics. Moreover, the extended quadrupolar π system of this class of dyes has facilitated the construction of numerous supramolecular architectures with fascinating photophysical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
283
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 441 publications
(290 citation statements)
references
References 181 publications
(150 reference statements)
7
283
0
Order By: Relevance
“…This type of evolution in our constructs' UV−vis spectra was indicative of strong pi−pi stacking interactions between the adjacent PTCDIs. [2][3][4][5][6][7][8]36 With our model constructs in hand, we proceeded to perform constant temperature molecular dynamics simulations for the PTCDI subunits of Oligo2 and Oligo3 (Figure 3). For simplicity, we only considered the structures shown in Figure 3 (denoted as P1, P2, and P3), removing the alkyl tails on the PTCDIs, the 3′ alkanethiol functionalities, the 5′ polyadenine tracts, and the terminal phosphate groups (when appropriate).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This type of evolution in our constructs' UV−vis spectra was indicative of strong pi−pi stacking interactions between the adjacent PTCDIs. [2][3][4][5][6][7][8]36 With our model constructs in hand, we proceeded to perform constant temperature molecular dynamics simulations for the PTCDI subunits of Oligo2 and Oligo3 (Figure 3). For simplicity, we only considered the structures shown in Figure 3 (denoted as P1, P2, and P3), removing the alkyl tails on the PTCDIs, the 3′ alkanethiol functionalities, the 5′ polyadenine tracts, and the terminal phosphate groups (when appropriate).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[251] These covalent multichromophore ensembles will, however, not be discussed here as we put our focus on self-assembled H-and J-aggregates of PBIs as illustrative examples for dye-aggregate-based exciton transport systems. Towards such aggregate systems PBIs bear another advantage: These dyes are among the most strongly aggregating dye molecules known, showing sufficiently high binding constants not only in water [252] (where solvophobic effects prevail), but also in aliphatic and even in aromatic solvents. [253] Already in 2001, Würthner et al reported on the selfassembly of columnar aggregates of PBIs in methylcyclohexane (MCH).…”
Section: Supramolecular Systems: Perylene Bisimide H-and J-aggregatesmentioning
confidence: 99%
“…[ 4 ] Hydrogen-bonding as a supramolecular engineering tool is useful to control self-assembly and highly relevant to aqueous and biochemical systems. [ 5,6 ] Recently, we have found that indigo, [ 7 ] and some of its derivatives [ 8,9 ] demonstrate ambipolar transport in organic fi eldeffect transistors (OFETs), with mobility ranging from 0.01-0.4 cm 2 V -1 s -1 . We…”
mentioning
confidence: 99%